Geophysics on an experimental site - Mari Jean Luc; Gaudiani Pierre (E3S Web of Conferences, 2022)
APEC (Association Pédagogique et Expérimentale du Cher) has developed an experimental site, situated in the Cher region (France), both for the training of students and for professionals. The site is also used for experimental studies in near surface geophysics. The training in geophysics concerns the acquisition and processing of surface seismic data in 2D or 3D. On the site, two boreholes have been drilled for logging experiments, such as Vertical Seismic Profile (VSP), Full Waveform Acoustic logging (FWAL). During the drilling, some parameters such as rate of penetration (ROP) and Torque have been continuously recorded. The completion of the two boreholes is different to evaluate the behaviour of logging tools with the change of completion (open hole, steel cased hole, slotted PVC cased hole). After a short review of seismic experiments done on the site, the paper is focused on logging data and shows how the completion can modify the answer of the logging tools (acoustic and electrical tools). In acoustic logging, the comparison of acoustic data recorded in slotted PVC cased hole and in open hole shows that the prediction of shear formation velocity from Stoneley waves can be done in open hole. In case of a completion with slotted PVC, the joints of PVC casing disturb the resistivity measurements. A specific procedure has been developed to filter the casing disturbances.